1982
DOI: 10.2170/jjphysiol.32.519
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of shivering as a cause of metabolic suppression with norepinephrine in warm- and cold-acclimated rats.

Abstract: The metabolic response of warm-acclimated (25•Ž for 4 weeks) and cold-acclimated (5•Ž for 4 weeks) rats to infused norepinephrine (NE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It has been reported that administration of vasopressor substances such as norephinephrine and phenylephrine suppresses heat production through the sinoaortic baroreceptor reflex in unanesthethized animals (12,29,30,36). In 1984, Shido et al (31) demonstrated that the fall in T c after peripheral injection of AVP is greatly reduced after bilateral sinoaortic deafferentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that administration of vasopressor substances such as norephinephrine and phenylephrine suppresses heat production through the sinoaortic baroreceptor reflex in unanesthethized animals (12,29,30,36). In 1984, Shido et al (31) demonstrated that the fall in T c after peripheral injection of AVP is greatly reduced after bilateral sinoaortic deafferentation.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the effect of systemic AVP on T c could be attributed, at least in part, to the baroreflexive suppression of nonshivering thermogenesis. Because BAT is under sympathetic nervous system control (11,28), the lowered metabolism after vasopressin may be due to reduced sympathetic nervous activity in the tissue (30). On the other hand, Morrison (20) suggested that sympathetic activity to BAT is under weak baroreflex control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the mechanisms of suppression in peripheral tissues by this vasopressor hormone. It was reported that administrations of vasopressor substances such as norepinephrine and phenylephrine suppressed heat production through the sinoaortic baroreflex in the unanesthetized animals (WASSERSTRUM and HERD, 1977;HOHTOLA et al, 1980;SHIBATA, 1982;SHIBATA et al, 1982). The aim of this study was to elucidate whether the baroreflexive suppression of metabolism could be a dominant mechanism in producing a fall in body temperature after the intravenous injection of vasopressin in the unanesthetized rats.…”
mentioning
confidence: 93%
“…It has been shown that the T cor of animals can be lowered by changes in arterial blood pressure [23,24]. Romanovsky et al [25] have shown that in rats with endotoxin shock, a fall in T cor and a downward shift of threshold T cor for heat production were accompanied by moderate hypotension.…”
Section: Discussionmentioning
confidence: 99%